Automatic medication refills to improve glycaemic control among patients with diabetes and low medication adherence - Linnaea Schuttner; Ashok Reddy; Chatty O'Keeffe; Anna L Golob; John Geyer; Kaylen Nelson; Cassandra Song; Christopher Vanderwarker; Jacqueline Britton; Edwin Wong (BMJ Open Quality)
Background Medication adherence impacts health outcomes. Healthcare organisations implementing system-level interventions have potential for greater spread and sustainability than individual-level interventions. Within the integrated US Veterans Health Administration, a multidisciplinary team developed and evaluated a pilot quality improvement programme to assess the feasibility of automatic mailed prescription refills for patients with diabetes and low medication adherence (assessed by medication possession ratio <80%).Methods Patients were randomised to usual care with self-initiated refills versus automatic mailed refills for 6 months. Process outcomes included glycaemic control measures (HgbA1C), medication possession ratios for both automatic and self-initiated (reference) refills of medications, patient satisfaction and workforce effort (pharmacist time).Results Overall, 199 patients were randomised to automatic refills (n=99; 40 of whom participated) versus usual care (n=100). In multivariable analysis adjusting for baseline differences, after 6 months there was no difference in the proportion of patients with follow-up HgbA1C <8% (60.8% automatic refills vs 60.5% usual care, p=0.96). In the automatic refill group, the medication possession ratio for reference medicines was significantly higher than usual care (63.9% vs 54.5%, 95% CI (for difference) 3.1% to 15.9%, p<0.01).Conclusions Implications and lessons from this pilot programme include potential beneficial indirect effects from automatic medication refills on patient self-initiated refills of other medications; the importance of tailoring solutions to patient subgroups and specific adherence barriers; and recognition that the rapid deployment, iteration and evaluation of the project was facilitated by a multidisciplinary team embedded within an organisational learning health system.